El control de constitucionalidad en Colombia (2010)
From the very beginning of the concept of state, has sought a reference on which to rest the authority of this over other institutions, the current reference is the supremacy of the constitution which is immersed the origin, characteristics and foundations of constitutional control. This idea then evokes the effective protection of the Constitution through an institutional body, a protection that has evolved through different stages until it reaches the court and integral control of the constitution. In that vein Constitutional Control is characterized mainly by directly applying the constitution above all other rules of the nation, and thus its application and interpretation by the Constitutional Court obliging the other state bodies through the so-called constitutional precedents. In Europe under these precedents may point additives, hortatory and manipulative. Colombia has received and extended these theories through simple constitutional precedents, and partial or delayed by the preceding module which is the subject of interpretation, the inclusive constitutional precedent, the declaration of unconstitutional state of affairs and previous interpretation of fundamental rights. All of the above noted authority on the effects in time and space by the Constitutional Court itself.